2013
DOI: 10.1007/s10529-013-1189-3
|View full text |Cite
|
Sign up to set email alerts
|

Effective method for the isolation and proliferation of primary lung cancer cells from patient lung tissues

Abstract: We have developed a technique for isolating and culturing primary lung cancer cells extracted from patient tissue to facilitate anti-cancer drug development. Patient-derived lung cancer tissues were mechanically dissociated to 40-100 μm. Dispase was then used to isolate cultured lung cancer cell populations, which were re-plated on Matrigel-coated dishes containing N2-supplemented medium and growth factors. This method allows pure populations of primary non-small cell lung cancer cells to be grown in vitro. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…A study indicates [4] that media containing serum or growth factors promote the growth of fibroblasts, making it difficult to purify the required cell population in the co-culture state. H. Baillie-Johnson et al [6] cultured Small Cell Lung Cancer (SCLC) cell lines and found that when these fibroblasts began to overgrow, to transfer specimens growing in HITES+2.5% FCS to separate HITES alone for some period of time could inhibit fibroblast growth.…”
Section: Purification Methods and Biological Characters Detection Of Primary Lung Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study indicates [4] that media containing serum or growth factors promote the growth of fibroblasts, making it difficult to purify the required cell population in the co-culture state. H. Baillie-Johnson et al [6] cultured Small Cell Lung Cancer (SCLC) cell lines and found that when these fibroblasts began to overgrow, to transfer specimens growing in HITES+2.5% FCS to separate HITES alone for some period of time could inhibit fibroblast growth.…”
Section: Purification Methods and Biological Characters Detection Of Primary Lung Cancer Cellsmentioning
confidence: 99%
“…PingWang et al [7] found that the culture medium of Defined Keratinocyte-Serum Free Medium (DK-SFM) did support the selective growth of typical epithelial cells and significantly inhibited the growth of fibroblasts coexisting. Joseph Seo et al [4] indicated that replacing serum with N2 supplements prevented fibroblast proliferation while allowing lung cancer cells to grow. As a result, the N2-supplemented was superior in purification while the BEI medium of 10% FBS was the first-rank culture medium in proliferation.…”
Section: Purification Methods and Biological Characters Detection Of Primary Lung Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first attempt to solve the disadvantage of cell line "purity" as well as personalization of the treatment approach was the introduction of primary ex vivo cancer cell lines into the cancer research, including drug testing, discovery and therapy response prediction, with improving methodologies and optimizations for cell culturing [175][176][177][178]. Heterogeneity found in cell cultures was suggested to be coded by biological mechanisms from the primary tumors, and it was acknowledged as an instrument for clinical implications.…”
Section: D In Vitro Modelsmentioning
confidence: 99%